Sustainable Universities _The GreenMetric Tool As a Strategic Driver in HEIs Considering Different Realities - Marinez Cristina Vitoreli; Rodrigo Luiz Guarnetti; Enzo Barbério Mariano (Journal of Sustainability Perspectives, 2021)
In this work the considered concept of sustainability explores the relationships between economic development, environmental quality as well as social. Delineated by the UN in 1972, since then the subject has taken on great proportions, mainly due to its imminent urgency. In 2015 the theme was part of the UN's Sustainable Development Goals, making up the Agenda 2030. Recently, Higher Education Institutions have been compelled to offer their contributions, given their role in human formation. Considering GreenMetric's relevance since the beginning of its activities, its dimensions and indicators have offered relevant directions on the path of Sustainable Higher Education Institutions. Thus, the present work demonstrated, through the case study, how the dimensions and indicators proposed by GreenMetric could form part as an important strategic driver in the path of a Brazilian Higher Education Institution - Academic Center, located in the countryside of São Paulo State. Its registration at GreenMetric in 2019 allowed the same formulations of short, medium and long term strategies.